Dampak Kekerasan Orang Tua Terhadap Kondisi Mental Anak Dalam Keluarga dan Penanggulangan - Exina Ida Harta Hutabalian; Amoli Ndraha; Kristian Sukatman; Korina Sanosa; Piter Imanson Damanik (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
Parental child abuse leading to mental illness is a form of physical, emotional, violence experienced by a child from a parent or guardian that adversely affects the child's mental well-being. It can include various forms of behaviors that degrade, humiliate, or emotionally or physically harm the child. Violence against a child is also one of the most dominant cases and is found anytime, anywhere, almost everywhere in all provinces in Indonesia. If this violence occurs against a child, it will have a negative impact on the child. The child will experience a sense of trauma, excessive fear, closure, silence, mental disorders, passive communication, and even physical disability if the violence is in the form of physical violence. This is very ironic, considering that children who are the next generation of the nation, should get parental love, guidance and loving education so that this study aims to prevent physical violence against children and the need for countermeasures, both from the government and from the family or parents of children. This study aims to identify the impact of parental violence on children's mental state and explore coping strategies. The importance of preventing physical and emotional violence against children requires collaborative efforts between the government, families, and communities. Effective coping strategies include social support from the surrounding environment, psychological interventions such as counseling and therapy, and education and training on positive parenting. Strict and comprehensive child protection policies are also necessary to create a safe and supportive environment for children's development. By raising awareness of the negative impact of violence and implementing appropriate coping strategies, it is hoped that children can grow and develop optimally, free from violence, and ready to become the next generation of physically and mentally healthy nations.